Application of molecular imaging in immune checkpoints therapy: From response assessment to prognosis prediction. (August 2022) - Liu, Wan-Ling; Zhang, Yong-Qu; Li, Liang-Tao; Zhu, Yuan-Yuan; Ming, Zi-He; Chen, Wei-Ling; Yang, Rui-Qin; Li, Rong-Hui; Chen, Min; Zhang, Guo-Jun
Abstract: Recently, immune checkpoint therapy (ICT) represented by programmed cell death1 (PD-1) and its major ligands, programmed death ligand 1 (PD-L1), has achieved significant success. Detection of PD-L1 by immunohistochemistry (IHC) is a classic method to guide the treatment of ICT patients. However, PD-L1 expression in the tumor microenvironment is highly complex. Thus, PD-L1 IHC is inadequate to fully understand the relevance of PD-L1 levels in the whole body and their dynamics to improve therapeutic outcomes. Intriguingly, numerous studies have revealed that molecular imaging technologies could potentially meet this need. Therefore, the purpose of this narrative review is to summarize the preclinical and clinical application of ICT guided by molecular imaging technology, and to explore the future opportunities and practical difficulties of these innovations. Highlights: Molecular imaging has the potential to elucidate correlations with systemic PD-L1 levels compared to inadequate IHC. This review is to summarize the preclinical and clinical application of ICT guided by molecular imaging This review provides a comprehensive overview of the key issues in the selection of ICT beneficiaries for precise treatment.